Peran musik sebagai fasilitas dalam praktek dokter gigi untuk mengurangi kecemasan pasien (The role of music as a dental practice facility in reducing patient’s anxiety) - Eric Priyo Prasetyo (Dental Journal (Majalah Kedokteran Gigi), 2005)
The people generally tend to associate a dental practice with a strange clinical atmosphere and a range of strange looking instruments, and furthermore pain during dental treatments. This condition more or less raises an anxiety to the patient and affects the patient’s regular dental attendance. Since anxiety has a significant role to the perception of pain, many attempts to make the patients relax are therefore needed to be done. Along with the advanced era, the development of science and technology affects the world of dental practice. Dentists are encouraged to provide better dental services and treat their patients holistically. In order to fulfill this, additional facilities such as music are needed. It was found that patients who listened to the preferred music before, during, and after their dental treatment tended to have the lower rate of anxiety. This decreased anxiety was the result of greatly increased feelings of relaxation and calmness, since music could dramatically influence physiological and psychological processes. Music based on preference also provided most patients a non-threatening and pleasurable experience. Recently, music as part of dental practice has been widely used in America and Europe. This article is purposed to inform that music as an additional facility plays an important role in reducing the patient’s anxiety to provide better dental care and patient management.